AN ANALYSIS OF FEMINISM IN MAYA ANGELOU’S POEMS BY USING HISTORICAL AND BIOGRAPHICAL APPROACHES - Indiani Eka Permatasari (JURNAL ILMIAH BAHASA DAN SASTRA, 2016)
This study analyzes discrimination toward black woman which appears in Maya Angelou’s poems. In this case, the researcher chose three poems of Maya Angelou. Those are “Still I Rise”, “Phenomenal Woman”, and “Caged Bird”. In other to discover them, the study was conducted by using feminism theory and also historical and biographical approaches. It focuses on words, lines, and stanzas of the poems. The research was conducted with the following statement of problems: (1) What is the dominant type of feminism in Maya Angelou’s poems? (2) What are the reasons of using feminism perspective in Maya Angelou’s poems? (3) How are the images of black woman described in Maya Angelou’s poems?. The research design of this study is descriptive qualitative method because the researcher does not use statistical numerical but is requires descriptive analysis of the object. The reseach is conducted by descriptive qualitative because the result of the data is word, sentence, and language. After collecting the data from the poems, the reseacher put them into some groups which relates to the problem focuses. The researcher analyzes every datum by using content analysis. Based on the research questions mentioned above, the result of the study are as follows. First, the reseacher concludes that the dominant type of feminsm in Maya Angelou’s poem is Radical Feminism because discrimination toward black women are related to the bad history of black people. Second, the reasons of using feminism perspective by the poet is the image of her bad life experiences. The last result is the image of black woman in Maya Angelou’s poems which shows the discrimination toward woman in her era. The result of the study can be used as a reference in the research literature itselt in educational institution and so on. It also expected to be usefel in saveral ways. This study gives significance for the researcher to understand and provide more knowlegde about feminism. The study may be expected to give significance to the future researcher who conduct studies about literature focusing on feminism or on poems or in using biographical and historical approaches.